Pengaruh New Fraud Diamond Terhadap Potensi Kecurangan Laporan Keuangan - Yanto, Anggie Ardila; Nelvirita, Nelvirita (Universitas Negeri Padang, 2025)
This study aims to examine financial targets, nature of industry, earnings growth, and change of directors on financial statement fraud. This study uses quantitative methods to test theories and analyze the relationships between variabels. The population in this study is contruction companies listed on the Indonesia Stock Exchange for the 2020-2023 period. This study uses purposive sampling, there are 20 companies over a 4-year period and produces 80 observation data. The analysis technique used in this study is logistic regression analysis. The results of the study with logistic regression analysis show that the nature of industry variabel has a positive and significant effect on the pottential statement fraud. Meanwhile, financial targets, earnings growth, and chane of directors for financial statements fraud.